2022
DOI: 10.1007/s00706-021-02887-4
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the stereochemistry of zirconium oxysalts—part IV: syntheses and crystal structures of Zr2(OH)2(XO4)3·4H2O (X = S, Se), Zr(SO4)2·4H2O, and Zr(SeO3)2

Abstract: Zr2(OH)2(XO4)3·4H2O (X = S, Se), Zr(SO4)2·4H2O, and Zr(SeO3)2 were synthesized at low-hydrothermal conditions from mixtures of Zr2O2(CO3)(OH)2, the respective acids, and minor amounts of water. While Zr2(OH)2(XO4)3·4H2O (X = S, Se) and Zr(SO4)2·4H2O form crystals up to several tenths of a mm, Zr(SeO3)2 was mainly obtained as microcrystalline powder, single crystals rarely exceeded 10 μm in size. Samples were investigated by single-crystal X-ray techniques and in the case of Zr(SeO3)2 also by X-ray powder diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…During an ongoing series of investigations of zirconium sulfates and selenates(IV,VI), in part with additional cations Wildner 2018, 2023;Wildner and Giester 2019;Wildner et al 2022), also two hitherto unknown copper(II) salts were obtained as byproducts, i.e. a new modification of Cu(SeO4) and Cu(SeO3OH)2•6H2O which are presented in this paper.…”
Section: Introductionmentioning
confidence: 95%
“…During an ongoing series of investigations of zirconium sulfates and selenates(IV,VI), in part with additional cations Wildner 2018, 2023;Wildner and Giester 2019;Wildner et al 2022), also two hitherto unknown copper(II) salts were obtained as byproducts, i.e. a new modification of Cu(SeO4) and Cu(SeO3OH)2•6H2O which are presented in this paper.…”
Section: Introductionmentioning
confidence: 95%
“…18 Wildner, M. et al reported the preparation and single crystal structure analysis of only 10 μm ZrSe 2 O 6 microcrystals. 19 Performance and application studies of Zr/Hf selenites or tellurites are still limited.…”
Section: Introductionmentioning
confidence: 99%